THE FORMATION AND DEVELOPMENT OF THE NATIONAL ETRADA IN UZBEKISTAN (Academia Science Repository, 2023)
This article provides full information about the reforms in the field of culture and art in the Republic of Uzbekistan, the formation and development of national pop art, directions of national pop art, and the activities of artists who contributed to national pop art.